Explosive Behavior and Rational Bubbles: Evidence from the Serbian Hyperinflation at Daily Frequency - Petrović, Pavle; Mladenović, Zorica (Panoeconomicus, 2022)
Using recently developed right-tailed sequential unit root tests at daily frequency in the extreme portion of the Serbian hyperinflation, we found that the money supply and the exchange rate exploded while the economy was approaching the maximum of the inflation tax Laffer curve, and remained explosive while on the wrong, decreasing side of that curve throughout the end of the hyperinflation. Money supply exploded as government tried first to raise seigniorage to a new higher plateau, and subsequently to prevent, albeit unsuccessfully, a decline in seigniorage while the economy was sliding down the decreasing side of the Laffer curve.The rational bubble was not found as the exchange rate explosiveness was driven by the explosiveness of its fundamental value: current and expected future money supply. Thus, even the extreme portion of the Serbian hyperinflation was driven by ever expanding money supply in the government quest for additional seigniorage and not by the rational bubbles. Keywords: Explosiveness, Rational bubbles, Hyperinflation, Sequential unit root tests. JEL: C12, C22, E31, F31.